Postural responses exhibit multisensory dependencies with discordant visual and support surface motion - Keshner, Emily A.; Kenyon, Robert V.; Langston, Jessica (Journal of vestibular research, 2004)
The purpose of this study was to identify how the postural system weights coincident yet discordant disturbances of the visual and proprioceptive/vestibular systems. Eleven healthy subjects (25–38 yrs) received either fore-aft translations of an immersive, wide field-of-view visual environment (0.1 Hz, ± 3.7 m/sec), or anterior-posterior translations of the support surface (0.25 Hz, ± 15 cm/sec), or both concurrently. Kinematics of the head, trunk, and shank were collected with an Optotrak system and angular motion of each segment plotted across time. With only support surface translation, segmental responses were small (1°–2°) and mostly opposed the direction of sled translation. When only the visual scene was moving, segmental responses increased as the trial progressed. When the inputs were presented coincidentally, response amplitudes were large even at the onset of the trial. Mean RMS values across subjects were significantly greater with combined stimuli than for either stimulus presented alone and areas under the power curve across subjects were significantly increased at the frequency of the visual input when both inputs were presented. Thus, intra-modality dependencies were observed, such that responses to the visual inputs significantly increased and responses to the somatosensory signals reflected the stimulus amplitude only when the two inputs were combined. We believe it unlikely that the role of any single pathway contributing to postural control can be accurately characterized in a static environment if the function of that pathway is context dependent.